Clear cell renal carcinoma metastasis to the thyroid gland combined with papillary thyroid carcinoma - a case report - Mihailovic, Jasna; Novkovic-Ostojic, Sladjana; Starcevic, Ivana; Roganovic, Jelena; Stankov, Maja; Vasiljevic, Tijana; Zivojinov, Mirjana (Frontiers in Oncology, 2026)
Clear cell renal cell carcinoma (ccRCC) represents the most common subtype of renal malignancy. Although nephrectomy remains the standard primary treatment, distant metastases may occur years after the initial diagnosis. Metastasis of ccRCC to the thyroid gland is an uncommon clinical event. We report a rare case involving concurrent metastatic ccRCC to the thyroid combined with a papillary thyroid carcinoma. A 61-year-old male with a prior history of metastatic ccRCC to the pancreas was referred to our institution for evaluation of thyroid enlargement. The patient underwent thyroid lobectomy, and histopathological analysis confirmed metastatic ccRCC within the thyroid tissue. Nine months postoperatively, routine ultrasound follow-up revealed a multinodular goiter in the contralateral thyroid lobe. Following completion thyroidectomy, histological examination identified a papillary thyroid carcinoma, staged as pT1a. Due to disease progression and recurrence of pancreatic metastasis, the patient was subsequently treated with tyrosine kinase inhibitor therapy. At the most recent follow-up, the patient remained alive and in good clinical condition. Given that ccRCC can metastasize many years after the initial diagnosis, prolonged follow-up is essential, particularly in patients presenting with thyroid nodules. Since metastatic lesions may mimic primary thyroid malignancies, accurate preoperative diagnosis, including fine-needle aspiration cytology and cell block with immunohistochemistry, is critical for guiding management. Total thyroidectomy remains the most effective treatment for isolated ccRCC metastasis to the thyroid gland.